2014
DOI: 10.1111/ijac.12228
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Excess Li+ on Microwave Dielectric Properties of Ca0.16Sr0.04Li0.4Nd0.4TiO3 Ceramics

Abstract: The effect of excess Li + (d) on microstructures and microwave dielectric properties of Ca 0.16 Sr 0.04 Li 0.4 Nd 0.4 TiO 3 ceramics with d = 0.00125-0.0125 was investigated. XRD analysis showed that lattice parameters in a-axis, b-axis, and c-axis became longer by the addition of small amount of excess Li + . Ca 0.16 Sr 0.04 Li 0.4 Nd 0.4 TiO 3 ceramics with d = 0.0075 after being sintered at 1270°C showed the optimal values with e r = 138, Q.f = 1591 GHz, and s f = 52 ppm/°C. Impedance measurement indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Based on impedance spectroscopy analysis, D. C. Sinclair et al found that the grain shells and cores had contribution to the microwave dielectric properties and dielectric loss in the BaCo 1/3 Nb 2/3 O 3 ceramics . In the Ca 0.16 Sr 0.04 Li 0.4 Nd 0.4 TiO 3 ceramics, impedance analysis indicated that the grain regions showed the inhomogeneity in electrical properties and dielectric loss of the ceramic system were mainly derived from the semiconducting grain cores . The impedance spectroscopy was employed to establish the electrical microstructure of CaCu 3 Ti 4 O 12 ceramics and had shown them to be electrically inhomogeneous, containing semiconducting grains with insulating grain‐boundary regions .…”
Section: Introductionmentioning
confidence: 99%
“…Based on impedance spectroscopy analysis, D. C. Sinclair et al found that the grain shells and cores had contribution to the microwave dielectric properties and dielectric loss in the BaCo 1/3 Nb 2/3 O 3 ceramics . In the Ca 0.16 Sr 0.04 Li 0.4 Nd 0.4 TiO 3 ceramics, impedance analysis indicated that the grain regions showed the inhomogeneity in electrical properties and dielectric loss of the ceramic system were mainly derived from the semiconducting grain cores . The impedance spectroscopy was employed to establish the electrical microstructure of CaCu 3 Ti 4 O 12 ceramics and had shown them to be electrically inhomogeneous, containing semiconducting grains with insulating grain‐boundary regions .…”
Section: Introductionmentioning
confidence: 99%